HISTORICAL ENVIRONMENT OF CITIES IN THE DEVELOPMENT OF ADAPTATION , TRADITIONS (for example, cities skirts) (Municipal economy of cities (Technical science), 2013)
An important aspect of sustainable development is a historical context. Contextual approach is considered from the perspective of the dialogue of contemporary architecture to the historic environment. Historical and architectural heritage has now formed not only as individual monuments, as well as a complete and organized the historic part of town. Theoretical and methodological basis of functional , social and Reconstructive adaptation is essential for proper functioning and preservation of the historic environment of cities skirts.